2018
DOI: 10.1017/ice.2017.303
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Competing Treatment Strategies for Clostridium difficile Infection: A Systematic Review

Abstract: BACKGROUND Clostridium difficile infection (CDI) presents a substantial economic burden and is associated with significant morbidity. While multiple treatment strategies have been evaluated, a cost-effective management strategy remains unclear. OBJECTIVE We conducted a systematic review to assess cost-effectiveness analyses of CDI treatment and to summarize key issues for clinicians and policy makers to consider. METHODS We searched PubMed and 5 other databases from inception to August 2016. These searches wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 49 publications
1
25
0
3
Order By: Relevance
“…Accounting for the risk of recurrence favors fidaxomicin due to averted recurrence and its associated mortality and healthcare costs. Two recent systematic reviews of economic evaluations support our findings that fidaxomicin is a cost-effective option in initial and recurrent CDI [23] and FMT is cost-effective in recurrent CDI [24].…”
Section: Discussionsupporting
confidence: 85%
“…Accounting for the risk of recurrence favors fidaxomicin due to averted recurrence and its associated mortality and healthcare costs. Two recent systematic reviews of economic evaluations support our findings that fidaxomicin is a cost-effective option in initial and recurrent CDI [23] and FMT is cost-effective in recurrent CDI [24].…”
Section: Discussionsupporting
confidence: 85%
“…Comment: In the context of CDI, FMT has consistently been shown to be cost-effective compared with other potential therapeutic options, even when evaluated in a variety of global healthcare settings 64. Nevertheless, in most cases funding of FMT services has been historically provided ad hoc by teaching hospitals/academic centres, and FMT services sometimes run with a financial deficit 65 66.…”
Section: Resultsmentioning
confidence: 99%
“…Animal studies have indicated that the composition of the gut microbiota can affect host susceptibility to diseases,72 and human studies have consistently shown that FMT durably alters the microbiome of the recipient 73 74. FMT is unlike other treatments in that it was rapidly adopted for widespread clinical use, bypassing the drug-development process, which typically collects prospective efficacy and safety data on large numbers of patients before making a treatment available 64 75. Therefore, it is important to collect real-world evidence for the short- and long-term safety of the procedure.…”
Section: Resultsmentioning
confidence: 99%
“…[44][45][46][47][48][49][50][51][52] Another review that included only 4 studies about FMT in rCDI also concluded that FMT was cost-effective. 55 FMT was considered cost-effective if it was less expensive and more effective than other treatments (FMT was dominant). 44,47,48,52 Otherwise, FMT was more expensive but more effective compared with other treatments.…”
Section: Discussionmentioning
confidence: 99%